2015
DOI: 10.2169/internalmedicine.54.5174
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Deterioration of the Renal Function Caused by the Coexistence of Intratubular Amyloidosis and Myeloma Cast Nephropathy

Abstract: Multiple myeloma presents with various kidney injuries, including cast nephropathy, light chain deposition disease, and amyloidosis. Cast nephropathy is the most common form and mostly consists of monoclonal immunoglobulin light chains with Tamm-Horsfall protein. Immunoglobulin light chain (AL) amyloidosis may affect all compartments of the kidney, but it is rare in the tubuli. We herein present a rare case with rapid progression of renal failure caused by the co-occurrence of intratubular amyloidosis and cast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…5,6 Purely intratubular amyloid is viewed as an unusual variant of light chain cast nephropathy with no clinical significance and, accordingly, 'does not merit the diagnosis of renal amyloidosis since the amyloid is exclusively intratubular and not deposited in the renal parenchyma'. 7 However, the literature on this point only relies upon case reports 5,[8][9][10][11][12][13] and old clinicopathological studies, 6,[14][15][16][17][18][19] which did not properly assess the clinical significance of intratubular amyloid, especially its relationship with the occurrence of systemic light chain amyloidosis in extrarenal sites. Thus, we designed this retrospective study to evaluate the frequency of intratubular amyloid in light chain cast nephropathy biopsy specimens seen at a single academic institution, and to assess whether intratubular amyloid was associated with extrarenal systemic light chain amyloidosis.…”
mentioning
confidence: 99%
“…5,6 Purely intratubular amyloid is viewed as an unusual variant of light chain cast nephropathy with no clinical significance and, accordingly, 'does not merit the diagnosis of renal amyloidosis since the amyloid is exclusively intratubular and not deposited in the renal parenchyma'. 7 However, the literature on this point only relies upon case reports 5,[8][9][10][11][12][13] and old clinicopathological studies, 6,[14][15][16][17][18][19] which did not properly assess the clinical significance of intratubular amyloid, especially its relationship with the occurrence of systemic light chain amyloidosis in extrarenal sites. Thus, we designed this retrospective study to evaluate the frequency of intratubular amyloid in light chain cast nephropathy biopsy specimens seen at a single academic institution, and to assess whether intratubular amyloid was associated with extrarenal systemic light chain amyloidosis.…”
mentioning
confidence: 99%
“…From 1962 to 1980, LCACs were found in approximately 55 autopsy patients with MM, and in about 2/3 of these patients, amyloid casts were diagnosed only by methyl violet staining and/or thiocyanin T staining [7][8][9][10][11][12]. From 1980 to 2020, only 25 patients with LCACs caused by MM were identified (renal biopsy in 24 cases and autopsy in 1 case), and the diagnosis of amyloid casts in these patients was based on Congo red staining and/or electron microscopy [6,[13][14][15][16][17][18][19][20][21] (Table 1). In addition, in three other papers the authors mentioned that they also observed LCACs in some patients with renal damage caused by MM, but they did not provide a detailed description [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Under polarized light microscopy, ordinary light microscopy and fluorescence microscopy, Congo red staining exhibits apple green double refraction, brick red and bright red, respectively [19]. In addition to the abovementioned typical pattern, the amyloid deposits also have other distribution forms in the cast, such as lamination form, which can present as two or more layers, and sometimes in a tree-ring shape [6-10, 12, 19-21], and homogeneous form, which is composed of clumped homogeneous deposits distributed in the whole cast [6,12,17,19]. Electron microscopy shows numerous randomly arranged unbranched fibrils with a diameter of 8-12 nm in the amyloid structures of the casts [6, 13, 15-17, 19, 21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Myeloma nephropathy is relatively common complications in patients with MM. Generally, the majority of severe renal injuries in patients with multiple myeloma are associated with immunoglobulin (Ig) free light chains (FLCs) [9,10]. Substantial FLCs (nephrotoxic proteins) accumulated in the proximal tubular epithelium are responsible for most tubulointerstitial injuries.…”
Section: The Relationship Between Cystatin C and Myeloma Nephropathymentioning
confidence: 99%